2021
DOI: 10.21831/jpe.v9i2.37393
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and strategies of postgraduate students in online learning during the Covid-19 pandemic

Abstract: The ongoing online learning during the Covid-19 pandemic has become a separate catalyst for the development of education that utilizes technology in the current industrial 4.0 era. However, on the other hand, there are still many gaps in online learning during the Covid-19 pandemic. This research study aims to (1) explore the experiences of postgraduate students in online learning; (2) describe the negative impacts and barriers to online learning, along with strategies for dealing with them; and (3) observe th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 39 publications
(64 reference statements)
0
4
0
Order By: Relevance
“…A study conducted in Indonesia showed that students acquired negative physical and psychological impacts when learning online (Fathoni & Retnawati, 2021), including mental health issues (Chen & Lucock, 2022). For example, a study conducted in the United Kingdom showed that a little more than half of university students experienced a deterioration in mental health in 2020.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Indonesia showed that students acquired negative physical and psychological impacts when learning online (Fathoni & Retnawati, 2021), including mental health issues (Chen & Lucock, 2022). For example, a study conducted in the United Kingdom showed that a little more than half of university students experienced a deterioration in mental health in 2020.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction result data is presented in the form of a table consisting of several sub-themes. Data analysis refers to the analysis model of Bogdan & Biklen (1982) by conducting reductions, looking for sub-themes, and looking for relationships between sub-themes (Fathoni & Retnawati, 2021). The triangulation process occurs through delivery between respondents.…”
Section: Sensitivity To Communicationmentioning
confidence: 99%
“…One of the things that need special attention after the Covid-19 pandemic in the world of education is the interpersonal relationship between teachers and students. Educators' interaction with students has been reduced during the Covid-19 pandemic (Fathoni, Mustadi, & Kurniawati, 2021a, 2021bFathoni & Retnawati, 2021). Well-established interactions between educators and learners can increase learner engagement in the classroom (Tichavsky, Hunt, Driscoll, & Jicha, 2015), build emotional patterns that support the cognition of learners (Talidong & Toquero, 2020), reduce anxiety (Zeng, Hou, & Peng, 2016), and evoke positive emotions in educators and learners (Hagenauer, Hascher, & Volet, 2015).…”
Section:  Introductionmentioning
confidence: 99%
“…Even for research mode students, time management problems (Tseng et al, 2019) and lack of supervisor monitoring (Silinda & Brubacher, 2016) are the main issues of fully online learning. A study conducted by Fathoni and Retnawati (2021) shows that students experience negative physical and psychological effects as well as other technical problems such as internet problems, devices, interaction with lecturers, monitoring and implementation of learning activities during the pandemic. The transmission of this epidemic has caused stress, depression and anxiety among the community who have to face the fear of the adverse effects to come (Wang et.al, 2020).…”
Section: International Students In Universiti Teknologi Malaysia (Utm)mentioning
confidence: 99%